2020
DOI: 10.1177/0960327120938845
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of TRIM24 suppresses growth and induces apoptosis in acute myeloid leukemia through downregulation of Wnt/GSK-3β/β-catenin signaling

Abstract: Tripartite motif-containing protein 24 (TRIM24) has currently emerged as a crucial cancer-related gene present in a wide range of human cancer types. However, the involvement of TRIM24 in acute myeloid leukemia (AML) has not been well investigated. The present study aims to investigate the significance, cellular function, and potential regulatory mechanism of TRIM24 in AML. We found that TRIM24 expression was significantly upregulated in AML compared with normal tissues. AML patients with low expression of TRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 39 publications
(54 reference statements)
1
13
0
Order By: Relevance
“…More specifically, the GSK-3β inhibitor AR-A014418 held the capacity of eliminating the repressive role of si-SATB1-AS1 on AML cell resistance in the current report. Consistent findings were reported before where inactivation of GSK3β partially reversed the TRIM24 knockdownmediated antitumor effects in AML cells [38].…”
Section: Discussionsupporting
confidence: 91%
“…More specifically, the GSK-3β inhibitor AR-A014418 held the capacity of eliminating the repressive role of si-SATB1-AS1 on AML cell resistance in the current report. Consistent findings were reported before where inactivation of GSK3β partially reversed the TRIM24 knockdownmediated antitumor effects in AML cells [38].…”
Section: Discussionsupporting
confidence: 91%
“…While many of the SUMO-ID candidates show increased peptide intensity in PML NBs after ATO treatment, we observed that some of them decreased. IRF2BP2 and TRIM24, which has also been linked to AML 56,57 , showed reduced levels after ATO treatment, suggesting that they might undergo degradation. In line with this idea, the 11S proteasome components are recruited into mature PML NBs and their localization is enhanced with ATO treatment 58 , suggesting that mature PML NBs may also act as proteolytic sites.…”
Section: Discussionmentioning
confidence: 99%
“…Germline À/À mice develop hepatocellular carcinoma but have no hematopoietic phenotype [46] No High expression in AML reported, associated with poor survival [45] Targets p53 for degradation [44] Decreased proliferation in AML- Copyright © 2022 Wolters Kluwer Health, Inc. All rights reserved. [98].…”
mentioning
confidence: 99%